Sodium valproate induced Stevens Johnson syndrome and hepatitis in a pediatric patient: a case report - Mugada, Vinodkumar; Kakarparthy, Ravishankar; Ayinampudi, Bharath Kumar; Gunda, Anuradha (International Journal of Research in Medical Sciences, 2017)
Stevens Johnson syndrome is a life threatening IgE mediated hypersensitivity reaction affecting the skin and mucous membranes and should be considered in any child who has been on antiepileptic medication. A case of Stevens Johnson Syndrome and hepatitis following treatment with sodium valproate is presented. A 2 year old female pediatric patient suffering from atonic seizures and myoclonic seizures was treated with sodium valproate monotherapy. The patient reported skin peeling and rash since 15 days and yellowish discoloration of sclera since 7 days. Her laboratory investigations revealed abnormal hemoglobin levels, blood urea and liver function. Based on physical examination and laboratory findings it was diagnosed that she was suffering from sodium valproate induced Stevens Johnson Syndrome with hepatitis. The score of toxic epidermal necrosis (SCORTEN) criteria score was 1. She was treated with antihistamines, iron folic acid and topical liquid paraffin lotion.